Abbasid rural settlement in northern Qatar: seasonal tribal exploitation of an arid environment? - McPhillips, Stephen; Rosendahl, Sandra; Morgan, Victoria (Proceedings of the Seminar for Arabian Studies, 2015)
A contiguous archaeological horizon of rural settlement dated tentatively to between the eighth and ninth centuries AD has been identified by University of Copenhagen survey, mapping, and geomorphological work in north-western Qatar. Twenty individual sites exhibit architectural remains of a distinctive architectural character, and provide new evidence for how people lived in this arid to hyper-arid environment in the early Islamic period. Each site consists of linear arrangements of stone domestic structures situated in the vicinity of areas of rawdha (seasonal oasis pastures fed by shallow groundwater) and hand-dug wells, extending between c. 100 and 600 m in length and oriented approximately on the same south-west to north-east alignment. In many instances, later Islamic occupation has also been attested adjacent to each rawdha. Preliminary analysis of pottery samples suggests a relationship with phases of occupation identified at the large Abbasid settlement of Murwab, and reveals a rich range of ceramics and glass, some of which is likely to have been imported from Iraq or other locations in the Arabian Gulf. This paper synthesizes the different strands of data collected by survey work and provides some preliminary interpretations about the nature of settlement and subsistence in medieval Qatar, suggesting implications for the history of the broader Gulf region.